DNA methylation characteristics of primary melanomas with distinct biological behaviour. - Szilvia Ecsedi; Hector Hernandez-Vargas; Sheila C Lima; Laura Vizkeleti; Reka Toth; Viktoria Lazar; Viktoria Koroknai; Timea Kiss; Gabriella Emri; Zdenko Herceg; Roza Adany; Margit Balazs (PLoS ONE)
In melanoma, the presence of promoter related hypermethylation has previously been reported, however, no methylation-based distinction has been drawn among the diverse melanoma subtypes. Here, we investigated DNA methylation changes associated with melanoma progression and links between methylation patterns and other types of somatic alterations, including the most frequent mutations and DNA copy number changes. Our results revealed that the methylome, presenting in early stage samples and associated with the BRAF(V600E) mutation, gradually decreased in the medium and late stages of the disease. An inverse relationship among the other predefined groups and promoter methylation was also revealed except for histologic subtype, whereas the more aggressive, nodular subtype melanomas exhibited hypermethylation as well. The Breslow thickness, which is a continuous variable, allowed for the most precise insight into how promoter methylation decreases from stage to stage. Integrating our methylation results with a high-throughput copy number alteration dataset, local correlations were detected in the MYB and EYA4 genes. With regard to the effects of DNA hypermethylation on melanoma patients' survival, correcting for clinical cofounders, only the KIT gene was associated with a lower overall survival rate. In this study, we demonstrate the strong influence of promoter localized DNA methylation changes on melanoma initiation and show how hypermethylation decreases in melanomas associated with less favourable clinical outcomes. Furthermore, we establish the methylation pattern as part of an integrated apparatus of somatic DNA alterations.